ANALISIS TINGKAT KEPUASAN KONSUMEN DAN KINERJA WARKOP KEMANG MANADO (Analysis the Level of Consumer Satisfaction and Performance of Warkop Kemang Manado) - Christian David Parengkuan; Theodora M. Katiandagho; Ellen G. Tangkere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aimed to analyse the level of consumer satisfaction at Warkop Kemang Manado and to formulate performance improvements of Warkop Kemang Manado. This research was conducted from November 2019 until April 2020. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with 44 respondents using a questionnaire, while secondary data were obtained from the business management. The results showed that, the value of the Customer Satisfaction Index (CSI) was 83.53 percent. It generally fallen in the "Very Satisfied" criteria. Based on the results of the Importance Performance Analysis (IPA), the variables that need to be improved were the taste of food/beverage, the suitability of food/beverage prices, knowledge and explanation of the waitress to the menu, the availability and cleanliness of toilets, and the availability of parking facilities. Whereas, the variables that need to be maintained were Food/Beverage hygiene and food/beverage equipment, Waiter appearance, Waitress readiness, Waitress hospitality and politeness, and Warkop Cleanliness.Keywords: Consumer Satisfaction, Performance